Access to the right to education in female inmates of Colombia - Rodríguez-Naranjo, Jeimy Tatiana (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This research aims to establish the importance of the human right of access to education as a guideline of rehabilitation within the execution of the sentence of the female prison population of Colombia. In the context in which this research was established, reunite various social, economic, educational andcultural factors that affect the enjoyment of the right to freedom. An analysis is done from the legal field of human rights (positivization) and recognition of the female recluse as subjects of rights, aimed to highlight the importance of a proper process of rehabilitation through access to education that dignify the prison population in the use of their human rights, because the loss of freedom limits the exercise of social and civil rights and the chaotic crisis of overcrowding and inner prison violence. Many studies are cited and also the Universal Declaration of Human Rights, international agreements, national jurisprudence and various public policies on the use of the human right to education in prison; finally are cited relevant conclusions to this research.